Physicochemical characteristics of surface modified Dijah-Monkin bentonite - Alexander, Jock Asanja (Taylor and Francis Inc., 2016)
The aim of this study was the evaluation of the physicochemical characteristics of surface modified Dijah-Monkin bentonite clay. The clay was modified by calcination and treatment with hydrochloric acid. The natural and modified clays were characterized by x-ray fluorescence (XRF), Fourier transform infrared (FTIR), x-ray diffraction (XRD), electron dispersive x-ray (EDX), thermogravimetric analysis (TG), scanning electron microscopy (SEM), elemental composition, cation exchange capacity (CEC), Brunauer–Emmett–Teller (BET) specific surface area and methylene blue adsorption. The XRF displayed the presence of SiO2 and Al2O3 in the range of 61.6–65.6 wt% and 19.4–21.7 wt%, respectively. The FTIR spectra showed the existence of Al–OH, Al–O, Si–O, and Si–O–Si functional groups in all clay samples, confirming the presence of hydrated aluminosilicate in the clay. The BET surface area decreased from 23.5 to 17.1 m2/g after acid treatment, while the CEC of clay samples range between 40.7 and 20.2 mEq/100 g. The minerals present in clays are montmorillonite, quartz, kaolinite, and muscouvite. The maximum methylene blue adsorption were estimated as 59, 48, and 45.8 mg/g for natural, calcined, and acidified bentonite, respectively. The structural formula for one-layer unit of montmorillonite was determined as K0.722Ca0.155[Si7.686]iv[Al3.054Ti0.113(Formula presented.)]viO20(OH)4. The natural Dijah-Monkin bentonite is a promising adsorbent candidate for the removal of charged pollutants.